Job dissatisfaction and the older worker: baseline findings from the Health and Employment After Fifty study. Issue 8 (5th May 2016) - D'Angelo, Stefania; Coggon, David; Harris, E Clare; Linaker, Cathy; Sayer, Avan Aihie; Gale, Catharine R; Evandrou, Maria; van Staa, Tjeerd; Cooper, Cyrus; Walker-Bone, Karen; Palmer, Keith T
Abstract : Objectives: Demographic changes are requiring people to work longer. Labour force participation might be promoted by tackling sources of job dissatisfaction. We aimed to describe the epidemiology of job dissatisfaction in older British workers, to explore which perceptions of work contribute most importantly, and to assess possible impacts on health. Methods: Participants aged 50–64 years were recruited from 24 English general practices. At baseline, those currently in work (N=5437) reported on their demographic and employment circumstances, overall job satisfaction, perceptions of their work that might contribute to dissatisfaction, and their general health, mood and well-being. Associations of job dissatisfaction with risk factors and potential health outcomes were assessed cross-sectionally by logistic regression, and the potential contributions of different negative perceptions to overall dissatisfaction were summarised by population attributable fractions (PAFs). Results: Job dissatisfaction was more common among men, below age 60 years, those living in London and the South East, in the more educated and in those working for larger employers. The main contributors to job dissatisfaction among employees were feeling unappreciated and/or lacking a sense of achievement (PAF 55–56%), while in the self-employed, job insecurity was the leading contributor (PAF 79%). Job dissatisfaction was associated with all of the adverse health outcomes examined (ORs of 3–5), as were most of the negative perceptions of work that contributed to overall dissatisfaction. Conclusions: Employment policies aimed at improving job satisfaction in older workers may benefit from focussing particularly on relationships in the workplace, fairness, job security and instilling a sense of achievement.